Mexico - Stein, R. Conrad (Chicago : Childrens Press, 1984)
An introduction to the geography, history, economy, culture, government, and people of the very varied country of Mexico.
Includes index.
Booklist.
School Library Journal.
6.0
5-8
5-9.
Keywords: Mexico -- Juvenile literature; Mexico; Mexico